2022
DOI: 10.1016/j.clml.2021.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Residual Disease in Multiple Myeloma: Potential for Blood-Based Methods to Monitor Disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Thus, bone marrow assessment for tumor plasma cell (TPC) burden at diagnosis and response monitoring has become an integral part of laboratory work‐up in PCNs. However, BM‐TPC enumeration has several challenges that limit accurate and reproducible results, including patchy involvement, hemodilution, TPC adherence to lipid‐enriched spicules, and so forth 4,14–17 . In addition, BM aspiration is a painful procedure and may not be feasible to perform multiple times for sequential response monitoring 17–19 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, bone marrow assessment for tumor plasma cell (TPC) burden at diagnosis and response monitoring has become an integral part of laboratory work‐up in PCNs. However, BM‐TPC enumeration has several challenges that limit accurate and reproducible results, including patchy involvement, hemodilution, TPC adherence to lipid‐enriched spicules, and so forth 4,14–17 . In addition, BM aspiration is a painful procedure and may not be feasible to perform multiple times for sequential response monitoring 17–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that CTPC possesses stem cell‐like features and altered genetic characteristics with high clonogenic potential 18,19,24–28 . The utility of periodic MRD assessment is increasing in myeloma with emerging MRD‐related treatment decisions 15,17,29–32 . The ability to detect MRD in the PB (PBMRD) can improve ease of testing and holds the potential to decrease the number of painful BM procedures 18 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations